The Influence of Students' Attitudes And Motivation of Grade X Fashion Design Department At Smk N 10 Medan On Their Interest In Entrepreneurship In The Fashion Field - Yesi Tri Cahya; Tri Utari Ismayuni (International Journal of Science and Environment (IJSE), 2025)
The purpose of this research is to assess how attitude and motivation impact interest in entrepreneurship within the fashion industry for grade X students in the Fashion Design Department at SMK Negeri 10 Medan. The study involved a total of 69 participants. A quantitative research method was employed, using a survey approach that included distributing a questionnaire. The data were examined using SPSS, which involved validity and reliability assessments, classical assumption tests (including heteroscedasticity and multicollinearity), and multiple linear regression analysis. The findings indicated that (1) attitude significantly and positively influences entrepreneurial interest (sig. 0.014 < 0.05), (2) motivation also has a significant and positive influence on entrepreneurial interest (sig. 0.001 < 0.05), and (3) when considered together, both attitude and motivation have a notable impact on entrepreneurial interest (F count = 18.731; sig. 0.000 < 0.05). The determination coefficient (R²) is 0.395, indicating that 39.5% of the changes in entrepreneurial interest are accounted for by attitude and motivation.